Berat Karkas dan Lemak Abdominal Ayam Broiler yang diberi Tepung Jintan Hitam (Nigella sativa) dalam Ransum selama Musim Panas - S. Salam; A. Fatahilah; D. Sunarti; Isroli Isroli (Universitas Sebelas Maret (UNS), 2013)
This study aimed to determine the effect of the use of black cumin and antibiotics on carcassweight and abdominal fat of broilers during summer seasons. The material in this study were used 100 individuals unsex one-day old broiler strain CP 707, and the ration of broiler were added black cumin powder (BCP). The ration consisted of yellow corn, rice brand, soybean meal,palm oil, fish meal, calsium and top mix. The diet was protein energy with 22.91% protein and 2,994 kcal/kg for starter and 20,01% protein and 3.054kcal/kg for finisher. Experiment was conducted as a completely randomized design with 5 treatments (control, antibiotic without BCP, 2% BCP, 4%BCP and 6% BCP). Carcas weight and abdominal fat was measured on at 28 day of age. The resulted data was analysed by analysis of variance (ANOVA) with F test to know the effect of treatment, and when there were significant continous to Duncan multiple range test. The results showed that addition of black cumin (Nigella sativa) and antibiotics as a feed additive in ration cannot increase carcass weight and peesentase abdominal fat of broilers during summer seasons. level of black cumin 2-6% in the feed has the same ability to antibiotics against carcass weight and percentage of abdominal fat of broilers.Key words: Broiler, antibiotic, carcass weigth, abdominal fat